Digital Value Migration in Media, ICT and Cultural Industries: From Business and Economic Models/Strategies to Networked Ecosystems, 1st edition - Vukanovic, Zvezdan (Routledge, 2020)
Societies today are in a period of dynamic change, highly fluid and contested in moving from traditional to liberal and from local to global, as well as varying from highly developed to emerging market economies. Alongside and facilitating this is a rapidly and exponentially changing digital media industry, including new technologies, multi-platform distributions and advertising models.